A new species of Andinia (Pleurothallidinae) from Peru and an updated phylogenetic analysis of the genus with emphasis on subgenus Aenigma - Ocupa-Horna, Luis; Vieira-Uribe, Sebastián; Ward, Raven; Brose, Caroline; Wilson, Mark (Lankesteriana: International Journal on Orchidology, 2022)
A new species, Andinia peruviana, from Amazonas department, Peru, is described and illustrated. Updated phylogenetic analyses of nuclear internal transcribed spacer (nrITS) sequences in this study re-affirm the monophyletic nature of Andinia sensu lato and further support the previously proposed circumscription which incorporated genera Lueranthos, Masdevalliantha, Neooreophilus, and Xenosia. Andinia subgenus Aenigma was strongly supported in all analyses. The new species was determined phylogenetically to belong to subgenus Aenigma, along with A. barbata, A. dalstroemii, A. hirtzii, A. pogonion, A. schizopogon and A. uchucayensis. The phylogenetically-confirmed representatives of subgenus Aenigma are illustrated with drawings and photographs, and their geographic distribution is discussed. The updated phylogenetic analyses also show the corrected phylogenetic positions of A. vestigipetala, as the sole representative of the clade corresponding to subgenus Minuscula, and A. trimytera, as a member of the clade corresponding to subgenus Andinia.